Catalog of the Opilioacarida (Acari: Parasitiformes) - de Araújo, Marcel Santos; Palma, Antonella Di; Feres, Reinaldo José Fazzio (Zootaxa, 2020)
A catalog of the described Opilioacaridae species and their type depository institutions is presented. Opilioacaridae comprises 53 valid taxa (with 2 subspecies and 3 fossil species) distributed in 13 genera. The zoogeographical distribution, described life stages and years of description are also provided and discussed. Recent work on the American continent has resulted in a great diversity from these zoogeographical zones, but the family has a worldwide distribution. In addition, we move Neocarus ojastii Lehtinen, 1980 into Caribeacarus, i.e., Caribeacarus ojastii (Lehtinen, 1980) n. comb.